Praanggapan dalam Novel Al-Yaum al-Mau’ud Karya Najib al-Kailani (Kajian Pragmatik) - Rohayanti, Wulan; Rachtikawati, Yayan; Indra Gunawan (Departement of Arabic Language and Literature, 2025)
This study aims to describe and illustrate the meaning of presumption along with the context contained in the presumption in the novel Al-Yaum al-Mau'ud by Najib Kailani. This research is a descriptive qualitative research. The descriptive qualitative method in this research leads to two steps to obtain data, namely data collection and data analysis. In the data collection technique, namely using the listening method in which there are tapping techniques and recording techniques. While in data analysis using extralingual pairing method. From the analysis of this research, there are existential presuppositions, which are dominated by direct speech that always shows the actual situation and existence. Then there is factual presumption in which it is dominated by literal direct speech, and all the speech is in the form of sentences, both in the form of single sentences and compound sentences. The sentence contained in the speech is intended to inform a news that is believed to be true. The non-factual presupposition is dominated by literal indirect speech. So, the sentence in the speech is a news sentence spoken in an inappropriate form, but there is a similarity between the meaning and the action. Then lexical presumption, in this presumption is dominated by direct speech which is accompanied by affirmation in the speech. Structural presumption is dominated by statements through speech in the form of interrogative sentences. As well as the factual counter presumption only has a definite marker, namely the presence of the lingual unit “if”.